Election Logistics Distribution Strategy in Indonesia : A Literature Review - Erviana, Ya Hanna; Astrid Meliani Basrani; Tamba, Angela BR; Wulandari, Wanda; Sinaga, Jona Bungaran Basuki (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia's electoral process relies heavily on good logistics management and high levels of participation. This study employs a qualitative descriptive approach through a systematic literature review, utilizing Publish or Perish software to identify and analyze relevant studies published between 2019 and 2024. The findings emphasize critical strategies such as selecting strategic warehouse locations, mapping distribution areas, and enhancing coordination among election organizers to ensure the timely and efficient delivery of election logistics to polling stations. Challenges such as geographical barriers, infrastructure limitations, and extreme weather persist, especially in remote regions. Additionally, voter participation can be improved through technology-based outreach strategies, accurate voter data update, and the active involvement of democracy volunteers. Despite limited internet access in certain areas, these methods have proven effective in raising awareness and engagement. By integrating strengthened logistics infrastructure, organizer training, and inclusive outreach strategies that utilize both digital tools and direct campaigns, this study offers practical recommendations to enhance the efficiency, inclusiveness, and sustainability of electoral processes in Indonesia. These findings serve as a valuable reference for future electoral reforms to uphold the transparency and democratic principles